Isocitrate dehydrogenase-1 mutations as prognostic biomarker in glioblastoma multiforme patients in West Bohemia - Polivka, J; Polivka, J; Rohan, V; Pesta, M; Repik, T; Pitule, P; Topolcan, O (BioMed research international, 2014)
INTRODUCTION: Glioblastoma multiforme (GBM) is the most malignant primary brain tumor in adults. Recent whole-genome studies revealed novel GBM prognostic biomarkers such as mutations in metabolic enzyme IDH-isocitrate dehydrogenases (IDH1 and IDH2). The distinctive mutation IDH1 R132H was uncovered to be a strong prognostic biomarker for glioma patients. We investigated the prognostic role of IDH1 R132H mutation in GBM patients in West Bohemia. METHODS: The IDH1 R132H mutation was assessed by the RT-PCR in the tumor samples from 45 GBM patients treated in the Faculty Hospital in Pilsen and was correlated with the progression free and overall survival. RESULTS: The IDH1 R132H mutation was identified in 20 from 44 GBM tumor samples (45.4%). The majority of mutated tumors were secondary GBMs (16 in 18, 89.9%). Low frequency of IDH1 mutations was observed in primary GBMs (4 in 26, 15.3%). Patients with IDH R132H mutation had longer PFS, 136 versus 51 days (P < 0.021, Wilcoxon), and OS, 270 versus 130 days (P < 0.024, Wilcoxon test). SUMMARY: The prognostic value of IDH1 R132H mutation in GBM patients was verified. Patients with mutation had significantly longer PFS and OS than patients with wild-type IDH1 and suffered more likely from secondary GBMs.
Keywords: senioři; Brain Neoplasms; isocitrátdehydrogenasa; Glioblastoma; senioři nad 80 let; Retrospective Studies; Prognosis; Česká republika; Kaplan-Meier Estimate; Isocitrate Dehydrogenase; Middle Aged; mužské pohlaví; Kaplanův-Meierův odhad; Adult; Czech Republic; glioblastom; Biomarkers, Tumor; Aged, 80 and over; ženské pohlaví; nádorové biomarkery; prognóza; retrospektivní studie; Humans; lidé středního věku; nádory mozku; dospělí; Female; Aged; lidé; Male